2020
DOI: 10.1177/0145561320927907
|View full text |Cite
|
Sign up to set email alerts
|

Location of the Sphenoid Sinus Ostium in Relation to Adjacent Anatomical Landmarks

Abstract: Purpose: The variability of sphenoid pneumatization and its relationship with the surrounding structures has been suggested. The aim of this study was to examine the effect of the surrounding bony structures on the position of the sphenoid ostium (SO). Methods: A prospective radiological review of computed tomography images of paranasal sinuses of 150 patients (300 sides) was conducted. Parameters investigated included the presence of Onodi cells, sphenoid rostrum pneumatization, and the type of sphenoid pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…20 Finally, obliteration of the sphenoethmoidal complex was the last variable investigated. The results found by Doubi et al 13 show the importance of carefully studying this area, as the presence of OCs can displace the sphenoid sinus ostium inferiorly. However, we observed no statistically significant association between OC volume and obliteration of the sphenoethmoidal complex in the unilateral and bilateral groups.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…20 Finally, obliteration of the sphenoethmoidal complex was the last variable investigated. The results found by Doubi et al 13 show the importance of carefully studying this area, as the presence of OCs can displace the sphenoid sinus ostium inferiorly. However, we observed no statistically significant association between OC volume and obliteration of the sphenoethmoidal complex in the unilateral and bilateral groups.…”
Section: Discussionmentioning
confidence: 91%
“…Results from earlier studies 9 11 12 13 14 indicated that there is an equal distribution between genders regarding the anatomic variation of OCs. The present study is in agreement with these results, as we found no statistically significant association between cell volume and gender for the unilateral and bilateral groups.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, obliteration of the sphenoethmoidal complex was the last variable investigated. The results found by Doubi et al [13] show the importance of carefully studying this area as the presence of OC can displace the sphenoid sinus ostium inferiorly. However, we observed no statistically signi cant association between OC volume and obliteration of the sphenoethmoidal complex for unilateral and bilateral groups.…”
Section: Discussionmentioning
confidence: 92%
“…Results from earlier studies [11,9,[12][13][14] indicated that there is an equal distribution between genders for anatomic variation of OCs. Our study is in agreement with these results, as we found no statistically signi cant association between cell volume and gender for unilateral and bilateral groups.…”
Section: Discussionmentioning
confidence: 95%